Senegal : Indigenous Language and Literature as a Non-Profit Business - The ARED Story - Easton, Peter; Fagerberg-Diallo, Sonja (World Bank, Washington, DC, 2017)
The note briefly describes the Associates in Research and Education for Development - ARED - experience, as well as that of the Center for Studies on Research and Development of African Languages - CERFLA - working towards sustaining literacy education, in particular, within the "fulaphones" regions in Senegal, to preserve their native languages. The experience shows traditional culture is strong, despite its minority status, which has nonetheless revitalized the cultural context, and enhanced literacy education in native languages. ARED undertook efforts to publish, and disseminate textbooks, either written in, or translated into native languages, including French texts, covering subjects from literacy manuals, stories and novels, to the development of civil society, and treaties on local knowledge, and traditional practices, or religions. ARED's high points include deciphering the needs for such enterprise, based on strong institutional capacity in accounting and management, and, ironically, the information revolution has simplified, and sustained publication in African languages.